Seismogenic Structure Orientation and Stress Field of the Gargano Promontory (Southern Italy) From Microseismicity Analysis - Miccolis, Simona; Filippucci, Marilena; de Lorenzo, Salvatore; Frepoli, Alberto; Pierri, Pierpaolo; Tallarico, Andrea (Frontiers in Earth Science, 2021)
Historical seismic catalogs report that the Gargano Promontory (southern Italy) was affected in the past by earthquakes with medium to high estimated magnitude. From the instrumental seismicity, it can be identified that the most energetic Apulian sequence occurred in 1995 with a main shock of MW = 5.2 followed by about 200 aftershocks with a maximum magnitude of 3.7. The most energetic earthquakes of the past are attributed to right-lateral strike-slip faults, while there is evidence that the present-day seismicity occur on thrust or thrust-strike faults. In this article, we show a detailed study on focal mechanisms and stress field obtained by micro-seismicity recorded from April 2013 until the present time in the Gargano Promontory and surrounding regions. Seismic waveforms are collected from the OTRIONS Seismic Network (OSN), from the Italian National Seismic Network (RSN), and integrated with data from the Italian National Accelerometric Network (RAN) in order to provide a robust dataset of earthquake localizations and focal mechanisms. The effect of uncertainties of the velocity model on fault plane solutions (FPS) has been also evaluated indicating the robustness of the results. The computed stress field indicates a deep compressive faulting with maximum horizontal compressive stress, SHmax, trending NW-SE. The seismicity pattern analysis indicates that the whole crust is seismically involved up to a depth of 40 km and indicates the presence of a low-angle seismogenic surface trending SW-NE and dipping SE-NW, similar to the Gargano–Dubrovnik lineament. Shallower events, along the eastern sector of the Mattinata Fault (MF), are W-E dextral strike-slip fault. Therefore, we hypothesized that the seismicity is locally facilitated by preexisting multidirectional fractures, confirmed by the heterogeneity of focal mechanisms, and explained by the different reactivation processes in opposite directions over the time, involving the Mattinata shear zone.